Place of death in patients with lung cancer: a retrospective cohort study from 2004-2013 - O'Dowd, Emma L.; McKeever, Tricia M.; Baldwin, David R.; Hubbard, Richard B. (Public Library of Science, 2016)
Introduction: Many patients with cancer die in an acute hospital bed, which has been frequently identified as the least preferred location, with psychological and financial implications. This study looks at place and cause of death in patients with lung cancer and identifies which factors are associated with dying in an acute hospital bed versus at home.